Persepsi Mahasiswa Riau Terhadap Seni “Kayat” Dan Kebudayaan Kuantan Dalam Upaya Pelestarian Budaya Kuantan Singingi - Destita Mutiara; Seri Hartati; Diki Arisandi; Muthmainnah Muthmainnah (EL-EMIR Institute, 2026)
This study aims to analyze students’ perceptions in Riau Province toward the traditional art of Kayat and the culture of Kuantan Singingi as part of efforts to preserve local culture. The method employed in this study is a quantitative approach with a survey design. Data were collected through the distribution of questionnaires to students from several universities in Riau, selected using purposive sampling. The research instrument was developed based on perception indicators, including knowledge, attitudes, and interest in the traditional art of Kayat. The results indicate that, in general, students have a fairly positive perception of Kayat as part of regional cultural identity. However, the level of students’ understanding of the philosophical values and cultural meanings embedded in Kayat remains moderate to low. In addition, students’ interest in directly participating in cultural preservation activities is not yet optimal. Factors influencing these perceptions include limited access to information, lack of exposure to cultural performances, and the dominance of popular culture in the digital era. Therefore, more innovative preservation strategies are needed, including the integration of digital technology, strengthening cultural literacy in higher education, and fostering collaboration among government, academics, and cultural communities.